Aktualisasi Ilmu Nahwu dalam Kehidupan Sehari-hari - Zen, Hamdy M (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2023)
Nahwu science is a branch of knowledge in Arabic that discusses Arabic grammar, including sentence structure, types of words, and grammatical rules in that language. Nahwu is very important in understanding and mastering Arabic grammar well, so that someone can understand thetexts of the Koran, hadith and other Arabic literature. Some general problems in nahwuscience are: Some concepts in nahwu are abstract and require in-depth understanding,such as the concepts of isim and fi'il, as well as the relationship between the two. This canbe a challenge for beginners. Understanding nahwu science is often closely related toArabic vocabulary. Learners need to have adequate knowledge of the vocabulary andmeaning of words in Arabic to be able to fully understand the sentence structure.Punctuation in Arabic sentences has a very important role in determining meaning.Differences in the use of punctuation marks, such as the waqaf sign (stop sign) and thetanwin sign, can significantly influence the meaning of a sentence. This researchdescribes the concept of actualizing Nahwu knowledge in everyday life, focusing onaspects of I'rob and mabni and discussing the logical implications of Nahwu concepts,such as being at the top, and starting from the bottom, being at the forefront, andmaintain decisions. Through real case analysis, the author explains how these conceptscan be applied to shape character, understand social life, and create positive change.Through the science of nahwu, it can help in understanding the grammatical structure ofthe Al-Qur'an. By understanding the rules of nahwu, readers can more deeplyunderstand the meaning and context of the verses of the Qur'an.